PEMEROLEHAN BAHASA KEDUA (BAHASA INDONESIA) PADA ANAK USIA 2 TAHUN - Park Jin Ryeo (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
This study aims to find out and describe the language acquisition system of children aged 2 years 3 months to 2 years 6 months, especially those that include phonology, morphology, and syntax. The research method used in this study is a qualitative method with a case study approach. After analyzing Lee Tae Yul's language acquisition ranging from phonological, morphological, and syntactic acquisition and production it was found that: 1) At the age of 2.5 years, a normal child can pronounce phonemes, and limited words according to their environment and objects the items around it; 2) At the age of 2.3 to 2.5 years, the words produced have begun to increase and start from nouns and verbs; 3) At the age of 2.5 years it seems, Lee Tae Yul has been able to string words in simple terms, starting from one, two to three words, and finally forming sentences.